2016
DOI: 10.1016/j.ophtha.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Gene Therapy for Leber Hereditary Optic Neuropathy

Abstract: Purpose Leber hereditary optic neuropathy (LHON) is a disorder characterized by severe and rapidly progressive visual loss when caused by a mutation in the mitochondrial gene encoding NADH:ubiquinone oxidoreductase subunit 4 (ND4). We have initiated a gene therapy trial to determine the safety and tolerability of escalated doses of an adeno-associated virus vector (AAV) expressing a normal ND4 complementary DNA in patients with a G to A mutation at nucleotide 11778 of the mitochondrial genome. Design In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
151
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(174 citation statements)
references
References 30 publications
4
151
0
19
Order By: Relevance
“…Furthermore, the retinal ganglion cell (RGC) promoter we describe here will benefit both basic research 32 and clinical gene therapies targeting RGCs. 33 …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the retinal ganglion cell (RGC) promoter we describe here will benefit both basic research 32 and clinical gene therapies targeting RGCs. 33 …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16]30 At least one of these vectors has also shown to be less immunogenic 31 and, in a recent phase I clinical trial, shown efficacy for the potential gene therapy of Leber's hereditary optic neuropathy. 32 We have also described strategies involving genome modifications that lead to the generation of ssAAV vectors with which high efficiency of transgene expression can be achieved. 17 In the present studies, we combined the two strategies to generate the optimized AAV vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Initial results from study NCT02161380 that treated five LHON patients carrying the G11778A mutation with ScAAV2-P1ND4v2 have been reported (Feuer et al 2016). At the 3-month time point, none of the patients lost vision and only minor adverse events were reported; these consisted of a transient increase of intraocular pressure (IOP), keratitis, subconjunctival hemorrhage, and a sore throat; a transient increase in neutralizing antibodies against AAV2 in 1 participant was also reported.…”
Section: Nd4 Gene Therapymentioning
confidence: 99%
“…Gene therapy has been proposed for treatment of LHON and active trials are currently enrolling subjects (Feuer et al 2015;Peragallo and Newman 2015;YuWai-Man et al 2014). Allotopic rescue is currently the modality being studied in the USA.…”
Section: Leber Hereditary Optic Neuropathy (Lhon)mentioning
confidence: 99%
See 1 more Smart Citation